Marginalized Youth. An Introduction. - Fabian Kessl; Hans-Uwe Otto (Social Work & Society, 2008)
The life conduct of marginalized groups has become subject to increasing levels of risk in advanced capitalist societies. In particular, children and young people are confronted with the harsh consequences of a "new poverty" in the contemporary era. The demographic complexion of today's poverty is youthful, as a number of government reports have once again documented in recent years in Australia, Germany, France, Great Britain, the US or Scandinavian countries. Key youth studies have shown a growing fear of the future among young people - especially with regard to the threat of unemployment and poverty. However, these results have not yet produced any fundamental critical political reaction.